PENERAPAN NILAI PENDIDIKAN KARAKTER DI TAMAN TAHFIDZUL QUR'AN AL-BUSYRO SUKOHARJO - Aina Salsabila; Indah Nurhidayati; S Samsuri (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
The purpose of this study is to understand and describe the character values applied in Tahfidzul Qur'an Park Surakarta. This research is a qualitative research with research subjects in Tahfidzul Qur'an Park Surakarta. Data were taken using observation, interviews and documentation. Meanwhile, data analysis is done by data reduction, data display and data verification. The results show that the implementation of character education is carried out through the planning, implementation, and evaluation processes. Then the model of implementing character education by including all programmed activities and habituation activities. While the learning methods and media used are storytelling, question and answer, role playing, assignment, field trip, and lecture methods. The supporting factor in the application of this character education is good and sustainable communication between the school and parents then there are obstacles in the application of the value of this character education, namely the lack of communication or the program has not been properly systemized.